Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.7863/jum.2008.27.10.1425
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Differentiation of Thyroid Nodules With Eggshell Calcifications

Abstract: Objective. The purpose of this study was to assess the role of known suspicious sonographic findings and to find other additional sonographic findings to differentiate benign and malignant thyroid nodules with "eggshell" calcifications. Methods. Our Institutional Review Board approved this retrospective study, and informed consent was not required. We reviewed sonographic findings of thyroid nodules in 795 patients who underwent thyroid surgery in our institution between August 2006 and February 2007. Ninety-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 11 publications
2
72
2
Order By: Relevance
“…Previously, peripheral calcification was thought to occur secondary to chronic degenerative changes and therefore indicate a benign status. However, recent studies have found that macrocalcifications including peripheral calcification might also be an indicator of thyroid nodule malignancy (9,10,(16)(17)(18)24,25). In this study, we showed that cytologically malignant and suspicious for malignancy results are observed more frequently in nodules with parenchymal macrocalcification.…”
Section: Evaluation Of Macrocalcification In Thyroid Nodulessupporting
confidence: 59%
See 3 more Smart Citations
“…Previously, peripheral calcification was thought to occur secondary to chronic degenerative changes and therefore indicate a benign status. However, recent studies have found that macrocalcifications including peripheral calcification might also be an indicator of thyroid nodule malignancy (9,10,(16)(17)(18)24,25). In this study, we showed that cytologically malignant and suspicious for malignancy results are observed more frequently in nodules with parenchymal macrocalcification.…”
Section: Evaluation Of Macrocalcification In Thyroid Nodulessupporting
confidence: 59%
“…In previous studies, histopathologically proven malignancy rate of thyroid nodules with peripheral macrocalcification was reported to range between 18.5% to 70% with most of studies showing higher than 50% malignancy rate in these nodules (8)(9)(10)23). Majority of carcinomas were papillary type, with a few follicular carcinoma histopathologically.…”
Section: Evaluation Of Macrocalcification In Thyroid Nodulesmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be difficult to distinguish from colloid but the presence of comet‐tail artifacts associated with colloid crystals may be helpful 2 , 13 . The association of macrocalcifications with thyroid cancer is less consistent 8 , 11 , 12 , 15 . However, recent data suggest that coarse calcifications and disrupted peripheral or “eggshell” calcifications are also markers of increased cancer risk 4 , 11 , 12 .…”
Section: Thyroid Ultrasoundmentioning
confidence: 99%